Independence, professionalism, professional skepticism - Agus Widodo Mardijuwono; Charis Subianto (Emerald Publishing Limited, 2018)
The purpose of this paper is to obtain empirical evidence of the relationship of independence, professionalism and skepticism with the quality of audit produced.This research was conducted with questionnaires distributed to all auditors working in KAP Surabaya and Sidoarjo. The population in this study was all auditors working in KAP 45 Surabaya and KAP 1 Sidoarjo. Hypothesis testing was performed by using the partial least square test with the help of SmartPLS software version 3.0.The results from this study found that auditor independence is positively related to audit quality but is not significant. Variable auditor professionalism is positively related to audit quality and proved significant, while the skepticism variable of auditor professionalism is positively related to audit quality and is significant.The results of this study indicate that auditor independence, professionalism and skepticism are positively related to audit quality.